Participative Decision Making and Employee Performance in Different Cultures: The Moderating Effects of Allocentrism/Idiocentrism and Efficacy - Lam, Simon S. K.; Chen, Xiaoping; Schaubroeck, John (Academy of Management Journal, 2002)
The relationship between perceived participative decision making and employee performance was examined in matched samples of employees from the Hong Kong and U.S. branches of one organization. Self-efficacy in regard to participating in decisions and idiocentrism moderated the relationship between perceived participative decision-making opportunity and individual performance. Perceptions of the participation efficacy of a work unit and allocentrism moderated the relationship between participative decision-making opportunity and group performance. Idiocentrism and allocentrism appeared to explain regional differences in how participative decision making and efficacy perceptions interacted to predict performance.